Integrated Control of River Overflow Based on Microcontroller - Sindak Hutauruk; Libianko Sianturi; Rido Oktovianus Habeahan (Electrical Engineering, Universitas Mercu Buana, 2023)
This river overflow control is carried out in stages and in an integrated manner. The river water level is detected in real time with four levels, namely normal, alert, standby, and beware. The overflow of river water at each level will flow automatically through three floodgates that work simultaneously, followed by turning on three water pumps which also work simultaneously. The water flowing from the floodgates is channeled into an irrigation area, while the pumped water is flowed into a reservoir. This river overflow control is carried out in an integrated manner between monitoring the river water level, opening and closing the floodgates, working the pump, and detecting the reservoir maximum level. When all the floodgates are fully open and all pumps are running, and the water level in the reservoir has reached the maximum limit, the alarm will sound. Such conditions are stated in a state of over flow or out of control. This control is based on a microcontroller so that it has a fast response with minimal components. The control system is designed and made in a miniature form that runs well and with a fast response time.